Symbolic Interaction and the Symbolic Codes of Turkish Modernization in the Context of Political Modernization (Third Sector Social Economic Review, 2025)
This study analyzes the modernization process that emerged during the founding of the Republic of Türkiye through symbols such as women, the alphabet reform, and the hat, based on symbolic interaction theory. Political symbols are effective tools in the interpretation of ideology, identity, values, and political attitudes within society. The Republic of Türkiye also resorted to various symbols while severing its cultural ties with the past and creating a new political culture program within the framework of its modernization goals. In this context, women were used as a symbol of social transformation in the effort to become Westernized. The alphabet reform was designed to create a new form of communication and transform cultural memory symbolically. With the introduction of compulsory hat-wearing, the hat became a political symbol and was accepted as the visual symbol of the modern individual. Symbols are polyphonic, multi-meaningful, and contextual. The symbol of women, which is examined in this study as a symbol of modernization, and the statements examined in the context of the Alphabet Reform and the Hat Law reveal the multiple meanings of symbols. These symbols have been used as both persuasive and coercive tools to instill the idea of modernization in society. Thus, they have served as powerful political symbols that express the difference between the traditional and the modern, while also highlighting the distinction between East and West. In this context, the study emphasizes the multiplicity of meanings of symbols and selects three of the many representations used in Turkish modernization as primary examples. It then discusses how political transformation and identity construction were achieved through these symbols.
Keywords: Symbolic interaction; political symbol; modernization; Türkiye; Rebuplic